Computer aided flow analysis in a clothes drier / Abd. Zamir Shaary and Azsarin Aziz - Shaary, Abd. Zamir; Aziz, Azsarin (Faculty of Mechanical Engineering, 1997)
The first chapter is more introduction about the Clothes Dryer and the proposal of this project and the problems with the existing design. All these will be explained in the following chapter. The explanation will give a brief idea on what it’s all about. The second chapter is about computer aided flow analysis. It’s also introducing what is the Fluent programming and how the project will be done by using Fluent programming. The third chapter is briefly about building the model of the Clothes Dryer machine. On this chapter we will try to give details about the computer model. The chapter I and the chapter 2 are important to give a rough idea on this project. The fourth chapter is more about the results and discussion. This chapter is about a presentation of result by using the photographs. The fifth chapter is on the conclusions of the analysis. The last chapter gives the scope for the future work.